2021
DOI: 10.7150/ijbs.57825
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid inhibits pyroptosis in spinal cord injury by augmenting autophagy via the AMPK-mTOR-TFEB signaling pathway

Abstract: Spinal cord injury (SCI) results in a wide range of disabilities. Its complex pathophysiological process limits the effectiveness of many clinical treatments. Betulinic acid (BA) has been shown to be an effective treatment for some neurological diseases, but it has not been studied in SCI. In this study, we assessed the role of BA in SCI and investigated its underlying mechanism. We used a mouse model of SCI, and functional outcomes following injury were assessed. Western blotting, ELISA, and immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 72 publications
3
61
0
Order By: Relevance
“…Neuronal death via pyroptosis or necroptosis is regulated through the activities of host proteins that induce different biological outcomes [ 67 ]. Autophagy, a prosurvival mechanism, has been found to suppress pyroptosis and necroptosis by degradation of various proteins (e.g., NLRP3, ASC, and RIPK1) [ 35 , 36 , 68 ]. Previous studies of SCI have confirmed that the induction of autophagy plays a neuroprotective role by suppressing apoptosis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal death via pyroptosis or necroptosis is regulated through the activities of host proteins that induce different biological outcomes [ 67 ]. Autophagy, a prosurvival mechanism, has been found to suppress pyroptosis and necroptosis by degradation of various proteins (e.g., NLRP3, ASC, and RIPK1) [ 35 , 36 , 68 ]. Previous studies of SCI have confirmed that the induction of autophagy plays a neuroprotective role by suppressing apoptosis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This work has several limitations that will require in-depth analyses. Specifically, in a previous study, TFE3 activation during SCI was found to be partially regulated by AMPK-SKP2-CARM1 and AMPK-mTOR signalling pathways [ 2 , 68 ]. In-depth investigations can delve into whether GDF-11 also acts through AMPK-SKP2-CARM1 and AMPK-mTOR signalling pathways and the differences among them in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is one of the main mechanisms of cell death and causes an acute inflammatory response by activating inflammasomes and releasing inflammatory cytokines (7). Previous studies have demonstrated that pyroptosis is involved in the occurrence and development of infectious diseases, cardiovascular diseases, cancer and numerous other diseases (8)(9)(10)(11)(12). Emerging studies suggest that toll-like receptors (TLRs) can be recognized as upstream signals by nucleotide-binding and oligomerization domain-like receptors (NLRs), which activate the assembly of the NLR pyrin domain containing 3 (NLRP3) inflammasome and caspase-1 and subsequently trigger pyroptosis (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CTSB inhibits autophagy by regulating the kinase ULK1 activity, and autophagy negatively regulates the activation of NLRP3 inflammasomes (Qi et al, 2016;Zhao et al, 2021). Similarly, recent evidence has illustrated that the use of autophagy inhibitors reversed the effect of betulinic acid, which reduces the activation of pyroptosis after SCI (Wu et al, 2021). However, evidence has shown that IL-1β release is not affected even in the absence of CTSB, thus casting doubt on the role of CTSB in NLRP3 inflammasome activation (Halle et al, 2008;Bauer et al, 2010;Hari et al, 2014).…”
Section: Lysosomal Damagementioning
confidence: 99%